'Locationally disadvantaged': planning governmentalities and peri-urban agricultural futures. Issue 3 (2nd July 2020) - Wynne, Laura; Ruoso, Laure-Elise; Cordell, Dana; Jacobs, Brent
ABSTRACT: Peri-urban areas are the interface between urban and rural regions, with these regions traditionally acting as foodbowls for adjacent urban areas. This peri-urban agriculture provides a diverse suite of benefits to urban areas. Increasingly, however, peri-urban areas are being converted to residential uses, driven in part by higher land values secured for land converted for residential development. In Sydney, planning and development has tended to treat peri-urban areas as 'suburbs in waiting'. Using a Foucauldian governmentality approach, this paper investigates the prevailing rationalities in metropolitan-level strategic planning documents—in particular A Plan for Growing Sydney and the Draft South West District Plan —and how these rationalities relate to peri-urban agriculture. Our analysis shows that the three overarching rationalities—the global city, the compact city and the sustainability agenda—frame the urbanisation of peri-urban agricultural lands as necessary and inevitable, and only integrate agriculture as part of the future of the city of Sydney when it can be rationalised within the 'global city' narrative. As a result, peri-urban areas are not considered to have unique planning needs, but are imagined as latent spaces that will enable Sydney to meet its housing and job targets through their future development.